2010
DOI: 10.1080/13588260903094418
|View full text |Cite
|
Sign up to set email alerts
|

Study on characteristics of a crashworthy high-speed train nose

Abstract: The external shape of a high-speed train nose is usually designed according to the aerodynamic considerations and to minimise the drag forces and noises. Crashworthiness of the nose is another aspect that is important from the passive-safety point of view. To improve the crashworthiness characteristics, usually there are not many options for changing the external shape of a high-speed train nose; therefore, a systematic study has been conducted to examine possible strategies in order to design crashworthy exte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 10 publications
0
16
0
Order By: Relevance
“…At present, many researches mainly focus on the crashworthy vehicles of trunk-railway [6,[11][12][13]23,31]. The research on the crashworthiness, strength and vibrational features of an aluminium railroad passenger car indicated that the stress values, natural frequencies and crashworthy characteristics of the aluminium structure were within the acceptable tolerances, but the final aluminium design was about one-third of the weight of the initial steel structure [4].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…At present, many researches mainly focus on the crashworthy vehicles of trunk-railway [6,[11][12][13]23,31]. The research on the crashworthiness, strength and vibrational features of an aluminium railroad passenger car indicated that the stress values, natural frequencies and crashworthy characteristics of the aluminium structure were within the acceptable tolerances, but the final aluminium design was about one-third of the weight of the initial steel structure [4].…”
Section: Introductionmentioning
confidence: 98%
“…The design of, and research into, crashworthy vehicles have become important issues around the world [6,8,12,13]. By improving the crashworthiness of passenger compartments, as well as setting energy-absorption devices and anti-climbing devices on specific railway vehicles [21,25], it is expected that most of the impact's kinetic energy can be absorbed and vehicle over-climbing can be avoided in the event of a collision.…”
Section: Introductionmentioning
confidence: 99%
“…the expansion tube has long-stroke, stable deformation mode and high specific energy-absorption capacity [7], [8]. Moreover, the expansion force of the tube is controllable and stable [9]- [11].…”
Section: Introductionmentioning
confidence: 99%
“…The responses and locations of weakness of the head vehicle and the middle vehicles in the same collision scenarios were compared, and three different collision behaviours of the head and middle vehicle were obtained, including different collision interfaces, different body structures and different collision sequences; structural improvement schemes were also investigated in their research (Xue et al 2007). Hosseini-Tehrani and Nankali (2010) noted that the head design of a high-speed train should not only consider the aerodynamic performance and noise but also the crashworthiness. The crashworthiness of 19 different internal/external structures and the sizes of head forms were systematically analysed.…”
Section: Introductionmentioning
confidence: 99%